Origin of sensory and autonomic innervation of the rat temporomandibular joint: A retrograde axonal tracing study with the fluorescent dye fast blue - Casatti, Cláudio Aparecido [UNESP]; Frigo, L.; Bauer, J. A. (American Association for Dental Research (AADR), 1999)
Previous studies that have used retrograde axonal tracers (horseradish peroxidase alone or conjugated with wheat germ agglutinin) have shown that the temporomandibular joint (TMJ) is supplied with nerve fibers originating mainly from the trigeminal ganglion, in addition to other sensory and sympathetic ganglia. The existence of nerve fibers in the TMJ originating from the trigeminal mesencephalic nucleus is unclear, and the possible innervation by parasympathetic nerve fibers has not been determined. In the present work, the retrograde axonal tracer, fast blue, was used to elucidate these questions and re-evaluated the literature data. The tracer was deposited in the supradiscal articular space of the rat TMJ, and an extensive morphometric analysis was performed of the labeled perikaryal profiles located in sensory and autonomic ganglia. This methodology permitted us to observe labeled small perikaryal profiles in the trigeminal ganglion, clustered mainly in the posterior-lateral region of the dorsal, medial and ventral thirds of horizontal sections, with some located in the anterior-lateral region of the ventral third. Sensory perikarya were also labeled in the dorsal root ganglia from C2 to C5. No labeled perikaryal profiles were found in the trigeminal mesencephalic nucleus. on the other hand, autonomic labeled perikaryal profiles were distributed in the sympathetic superior cervical and stellate ganglia, and parasympathetic otic ganglion. Our results confirmed those of previous studies and also demonstrated that: (i) there is a distribution pattern of labeled perikaryal profiles in the trigeminal ganglion; (ii) some perikaryal profiles located in the otic ganglion were labeled; and (iii) the trigeminal mesencephalic nucleus did not show any retrogradely labeled perikaryal profiles.
Keywords: temporomandibular joint; autonomic ganglia; sensory ganglia; fast blue; retrograde transport